Chanje Lavi Plantè in Haiti: Hillside soil conservation as a measure to increase yields and sequester carbon in Haiti - Nash, Julie; Grewer, Uwe; Galford, Gillian L.; Bockel, Louis (2016)
Analysis of the potential mitigation impacts of the agricultural development project Chanje Lavi Plantè in Haiti indicated that large amounts of carbon sequestration could be achieved through reforestation and perennial crop expansion. The project’s strategy for watershed and landscape restoration links investments in profitable orchard systems with hillside stabilization. Reforestation of watersheds (–478,828 tCO2e/yr) and perennial crop expansion (– 230,854 tCO2e/yr), drive 98% of the project’s sizable climate change mitigation co-benefits that are foreseen under successful project implementation.  Chanje Lavi Plantè’s reduction in postharvest loss contribute to the reduced GHG emission intensity of cropping systems (GHG emissions per unit of production). Interventions are estimated to reduce postharvest loss substantially in these value chains: plantain (– 53%), maize (–47%), rice (–44%), beans (–50%) and mango (–35%).  The investments made by the project in irrigation infrastructure, terracing, and forest plantations aim to increase financial revenues of beneficiaries and reinforce the lasting provision of ecosystem services.